EMAP: Expedite Message Authentication Protocol for Transport Unexpected Networks - Srinivas, A.; Babu, Stalin (IJRDO -Journal of Computer Science Engineering, 2015)
Vehicular ad hoc networks (VANETs) adopt the general public KeyInfrastructure (PKI) and Certificate Revocation Lists (CRLs) for his or her security. Inany PKI system, the authentication of a received message is performed by checking ifthe certificate of the sender is enclosed within the current CRL, and substantiating thegenuineness of the certificate and signature of the sender. during this paper, we have atendency to propose associate degree Expedite Message Authentication Protocol(EMAP) for VANETs, that replaces the long CRL checking method by associate degreeeconomical revocation checking method. The revocation check method in EMAP uses akeyed Hash Message Authentication Code HMACÞ, wherever the key employed inscheming the HMAC is shared solely between non revoked On-Board Units (OBUs).additionally, EMAP uses a completely unique probabilistic key distribution, that permitsnon revoked OBUs to firmly share and update a secret key. EMAP will considerablydecrease the message ratio owing to the message verification delay compared with thestandard authentication ways using CRL. By conducting security analysis andperformance analysis, EMAP is in contestable to be secure and economical